Nutritional deficiencies in iron overloaded patients with hemoglobinopathies - Claster, Susan (2009)
One of the hallmarks of both sickle cell disease (SCD) and thalassemia major (TM) is accelerated oxidative damage. Decreased antioxidant levels and increased oxidant stress biomarkers are found in both diseases. Although isolated vitamin deficiencies have been reported in TM and nontransfused SCD patients, a comprehensive evaluation of vitamin and trace mineral levels has never been performed in chronically transfused SCD or TM patients. As vitamins and trace minerals may be consumed as a result of chronic oxidative stress; we hypothesized that levels of these compounds would correlate with surrogates of iron overload, hemolysis, and inflammation in chronically transfused patients. Using a convenience sample of our group of chronically transfused patients we studied 43 patients with SCD (17 male, 26 female) and 24 patients with TM (13 male and 11 female). The age range for our patients varied from 1.5 to 31.4 years. Levels of vitamins A, thiamin, B6, B12, C, D, E as well as selenium, zinc, copper, and ceruloplasmin were measured. We found that 40–75% of the patients were deficient in A, C, D and selenium and 28–38% of the patients had low levels of B vitamins and folate. There was little association with iron overload, hemolysis, or inflammation. Although the precise mechanism of these deficiencies is unclear, they may contribute to the morbidity of chronically transfused hemoglobinopathy patients.